Chemical attack of Malaysian pozzolans concrete - Hilton Ahmad, Mohd (Penerbit UTHM, 2009)
Malaysia produces more than 10 million tonne of by-product from industrial sector per year. As the environmental impact concerns, more than half of the by-product can be recycled to be used as construction materials. One of them is pozzolan, a cement replacing material that can be used to enhance the properties of the concrete. This paper studies the chemical attack to local prozzolans concrete. The parameters studied include.weight loss, length change, and residual strength of local pozzolans concrete after been exposed to severe environment. The specimen were tested under normal room temperature, exposed to magnesium sulfate, MgSO4 where both sulfate attack and acid attack take place. Two series of pozzolans which is Pulverized fly ash (PFA) and Palm oil fuel ash (POFA) were identified. Another series of admixture, Quarry Dust (QD) from quarry waste that contain high amount of silica content also been carried out. Each series will study the effect of cement replacement percentage of 5%, 10% and 15%. The parameters were compared to conventional ordinary Portland cement (OPC) concrete as control mix. Accelerated testing was conducted at 3, 7, 28, 56 and 90 days. The result shows that the local pozzolans concrete were found to be in good resistance against sulfate attack compared to conventional concrete. Compared to all series conducted, series of PFA replacement gave the best resistance followed by POFA and QD replacement series.